Association of working hour characteristics and on-call work with risk of short sickness absence among hospital physicians: A longitudinal cohort study. (1st February 2022) - Ropponen, Annina; Koskinen, Aki; Puttonen, Sampsa; Ervasti, Jenni; Kivimäki, Mika; Oksanen, Tuula; Härmä, Mikko; Karhula, Kati
ABSTRACT: Physicians often work long hours and on-call shifts, which may expose them to circadian misalignment and negative health outcomes. However, few studies have examined whether these working hour characteristics, ascertained using objective working hour records, are associated with the physicians' risk of sickness absence. We investigated the associations of 14 characteristics of payroll-based working hours and on-call work with the risk of short sickness absence among hospital physicians. In this cohort study, 2845 physicians from six Finnish hospital districts were linked to electronic payroll-based records of daily working hours, on-call duty and short (1–3 days) sickness absence between 2005 and 2019. A case-crossover design was applied using conditional logistic regression with the 28 day case and control windows to estimate odds ratios (ORs) and 95% confidence intervals (CI) for short sickness absence. After controlling for weekly working hours and the number of normal (≤12 h) shifts, a higher number of long (>12 h) shifts (ORs for ≥5 versus none: 2.54, 95% CI 1.68–3.84), very long (>24 h) shifts (ORs for ≥5 versus none: 2.62, 95%CI 1.61–4.27), and on-call shifts (OR for ≥5 versus none: 2.15, 95% CI 1.44–3.21) and a higher number of short (<11 h) shift intervals (OR for ≥5 versus none: 12.61, 95% CI 8.88–17.90) were all associated with the increased risk of short sickness absence. These associations did not differ between male and female physicians or between age groups. To conclude, the findings from objective working hour records show that long work shifts, on-call shifts and short shift intervals are related to the risk of short (1–3 days) sickness absence among hospital physicians.